Experiences and Challenges in an NGO run Organ Donation Helpline. (July 2018) - Kanvinde, Hemal; Shroff, Sunil; Kumar, Pallavi; Jairam, Jaya
Abstract : Introduction: MOHAN Foundation a Non-Government Organisation in India set a free to caller organ donation helpline in August 2012 to promote organ donation. In the past 5 years the counselors have responded to more than ten thousand calls. Helplines offer professional and impartial support to callers. Methods: The helpline is supported by a database of information on eye-banks, skin banks, donation centres and NGOs. Calls are taken by trained counselors and transplant coordinators. Publicity of the number is via websites, print and TV campaigns on Organ donation. Regular debriefing and training keeps the staff motivated. Results: Callers use the internet and MOHAN Foundation to find the number (95%). Media campaign on organ donation has resulted in a spike in calls. More than 30% of callers are those who wish to register as donors. 30% of callers are patients or their family members with queries on organ procurement. Around 10% of calls are about trade in organs and organ donation after suicide. Around 10% of calls are about issues with real time cases of tissue and organ donation. Discussion: In todays's environment of outcome based funding, supporting the helpline has been one of the greatest challenges. India being a multilingual country, providing the service in all languages is another challenge. State governments of three states have shared this number in their official websites and have helped in increasing the reach of the helpline. Transplant coordinators also pitch in their time to answer calls which helps in reduction of costs. Adding a line in the welcome message that it is illegal to trade in organs has helped in reduction of such calls. Stories of donation through the helpline are added to the MOHAN Foundation website and this motivates the counselors to take the calls. Conclusion: Public education on organ donation, actual referrals for donation, queries on legal aspects can be done through a helpline. Well trained staff can push the program and get more people to register as donors.